A cost-effective chemo-thermo-poroelastic wellbore stability model for mud weight design during drilling through shale formations - Saeed Rafieepour; Siavash Zamiran; Mehdi Ostadhassan (Journal of Rock Mechanics and Geotechnical Engineering, 2020)
Drilling through chemically-active shale formations is of special importance due to time-dependent drilling fluid–shale interactions. The physical models presented so far include sophisticated input parameters, requiring advanced experimental facilities, which are costly and in most cases unavailable. In this paper, sufficiently-accurate, yet highly practical, models are presented containing parameters easily-derived from well-known data sources. For ion diffusivity coefficient, the chemical potential was formulated based on the functionality of water activity to solute concentration for common solute species in field. The reflection coefficient and solute diffusion coefficient within shale membrane were predicted and compared with experimental measurements. For thermally-induced fluid flow, a model was utilized to predict thermo-osmosis coefficient based on the energy of hydrogen-bond that attained a reasonably-accurate estimation from petrophysical data, e.g. porosity, specific surface area (SSA), and cation exchange capacity (CEC). The coupled chemo-thermo-poroelastic governing equations were developed and solved using an implicit finite difference scheme. Mogi-Coulomb failure criterion was adopted for mud weight required to avoid compressive shear failure and a tensile cut-off failure index for mud weight required to prevent tensile fracturing. Results showed a close agreement between the suggested model and experimental data from pressure transmission tests. Results from a numerical example for a vertical wellbore indicated that failure in shale formations was time-dependent and a failure at wellbore wall after 85 min of mud–shale interactions was predicted. It was concluded that instability might not firstly occur at wellbore wall as most of the conventional elastic models predict; perhaps it occurs at other points inside the formation. The effect of the temperature gradient between wellbore and formation on limits of mud window confirmed that the upper limit was more sensitive to the temperature gradient than the lower limit.